Enhancing Korea's Work Competency: Focusing on Problem-solving Skills - Yong-seong Kim (Korea Development Institute (KDI), 2017)
- This study attempts to explore the use of and underlying issues related to problem-solving skills, a vital competency in future jobs, and policy measures for improvement. - An international comparison shows that Korean workers (aged 16-65) are fairly good at utilizing their skills but poor at applying those skills to solve problems at work. - As problem solving is a key future competency, it is essential that the relevant skills are enhanced and actively utilized. - However, insufficient education and training opportunities, poor communication and cooperation at work and a dual labor market structure could become obstacles. - To enhance the use of problem-solving skills at work, concerted efforts at various levels are needed, for example changing the contents and methods of educational/training programs and establishing a skill-friendly labor market structure. - Educational/training programs need to provide more field experiences and professional knowledge as well as soft skills including collaboration, compromise and communication - Instead of a 'flexible adjustment of the workforce' through easy hiring and firing, labor reforms should be implemented though a 'flexible adjustment of working conditions' (i.e. wages and working hours) so that both employer and employee can accumulate and fully utilize the necessary skills in problem solving in a stable employment relationship.
Keywords: 330